2020
DOI: 10.1099/mgen.0.000421
|View full text |Cite
|
Sign up to set email alerts
|

Complete genome of a unicellular parasite (Antonospora locustae) and transcriptional interactions with its host locust

Abstract: Microsporidia are a large group of unicellular parasites that infect insects and mammals. The simpler life cycle of microsporidia in insects provides a model system for understanding their evolution and molecular interactions with their hosts. However, no complete genome is available for insect-parasitic microsporidian species. The complete genome of Antonospora locustae, a microsporidian parasite that obligately infects insects, is reported here. The genome size of A. locustae is 3 170 203 nucleotides, compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…Genomic and protein sequences from N. locustae and several other single-celled organisms were used to study evolutionary relationships in genetic synteny and collinearity using the MCScanX method. Results showed that within the microsporidia, most genes exhibit good collinearity [45].…”
Section: Genomics and Molecular Biologymentioning
confidence: 99%
See 2 more Smart Citations
“…Genomic and protein sequences from N. locustae and several other single-celled organisms were used to study evolutionary relationships in genetic synteny and collinearity using the MCScanX method. Results showed that within the microsporidia, most genes exhibit good collinearity [45].…”
Section: Genomics and Molecular Biologymentioning
confidence: 99%
“…Understanding the molecular biology of N. locustae is fundamental in determining its biology and molecular interactions with the host and improving applications in its use for pest control. A complete genomic sequence of N. locustae has recently been revealed by Chen et al [45], which is a major achievement. Sequencing of its genome yielded 3,170,203 nucleotides, encoding for 1857 predicted genes, of which 1755 are single-exon genes, and 102 are multiple exon genes.…”
Section: Genomics and Molecular Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…Paranosema ( Nosema ) locustae is an entomopathogenic fungus that only infects locusts. Since the 1980s, the fungus has shown great potential as a biological control in locust control ( 1 , 2 ). Locusts infected by P. locustae can spread the pathogen to other nearby locusts through horizontal transmission.…”
Section: Introductionmentioning
confidence: 99%
“…Microsporidia have an extremely reduced genome ranging from 2.3 to 23 Mb, indicating an extreme dependence of the parasite on the host for biochemical processes [3,4]. There have been significant advances in the parasitological, evolutionary, and genomic research on microsporidia since multiple genome sequences were sequenced [5][6][7][8][9][10][11][12][13]. In addition, transcriptomics analysis of microsporidia infection in hosts has revealed a complicated and interconnected interaction in which microRNA (miRNA) as a key gene expression regulator is involved.…”
Section: Introductionmentioning
confidence: 99%